2010
DOI: 10.1016/j.juro.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Perioperative Outcomes Following Radical Cystectomy: 90-Day Readmissions, Morbidity and Mortality in a Contemporary Series

Abstract: Readmission rates after radical cystectomy are significant, approaching 27% within the first 90 days. Gender and age adjusted Charlson comorbidity index were independent predictors providing preoperative information identifying patients more likely to require readmission or possibly to benefit from a longer initial hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
130
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(156 citation statements)
references
References 18 publications
20
130
3
3
Order By: Relevance
“…We confirmed the morbidity revealing a 22.8% readmission, 55.2% complication, and 2.3% in-hospital mortality rate, which is similar to other published series. [7][8][9]13,14 We also revealed that treatment at higher-volume centres or academic centres was not protective or predictive of readmission. Academic centres were less likely to discharge patients to PACFs, which may be protective.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…We confirmed the morbidity revealing a 22.8% readmission, 55.2% complication, and 2.3% in-hospital mortality rate, which is similar to other published series. [7][8][9]13,14 We also revealed that treatment at higher-volume centres or academic centres was not protective or predictive of readmission. Academic centres were less likely to discharge patients to PACFs, which may be protective.…”
mentioning
confidence: 69%
“…Radical cystectomy (RC) may face scrutiny since it is associated with complication rates up to 68% and readmission rates as high as 26% even when performed at centres of excellence. [7][8][9] Given this data, RC could be a target quality improvement area. Therefore, our objective was to determine patient-and provider-related factors associated with 30-day readmission after RC.…”
Section: Introductionmentioning
confidence: 98%
“…Patient and hospital-level characteristics of index readmitted, non-index readmitted, and all cystectomy patients. 4 [3,7] 4 [3,8] 4 [3,7] Mean Number of Readmissions during 90-day follow-up (SE) Table 3 Causes of index and non-index readmission using principal ICD-9 diagnosis code. …”
Section: Discussionmentioning
confidence: 99%
“…1 Despite refinements in surgical technique and perioperative management, RC has been associated with a substantial risk of postoperative morbidity and mortality, where the rates of short-term complications and mortality. [1][2][3][4][5][6][7] Identifying determinants of postoperative outcomes is crucial for individual risk-adjustment prior to RC. Several studies have reported predictors of complications, perioperative mortality, and readmission.…”
Section: Introductionmentioning
confidence: 99%